The moral belief problem - Sinclair, Neil (Blackwell, 2006)
The moral belief problem is that of reconciling expressivism in ethics with both minimalism in the philosophy of language and the syntactic discipline of moral sentences. It is argued that the problem can be solved by distinguishing minimal and robust senses of belief, where a minimal belief is any state of mind expressed by sincere assertoric use of a syntactically disciplined sentence and a robust belief is a minimal belief with some additional property R. Two attempts to specify R are discussed, both based on the thought that beliefs are states that aim at truth. According to the first, robust beliefs are criticisable to the extent that their content fails to match the state of the world. This sense fails to distinguish robust beliefs from minimal beliefs. According to the second, robust beliefs function to have their content match the state of the world. This sense succeeds in distinguishing robust beliefs from minimal beliefs. The conclusion is that the debate concerning the cognitive status of moral convictions needs to address the issue of the function of moral convictions. Evolutionary theorising may be relevant, but will not be decisive, to answering this question.